Hyaluronic acid-based antibacterial hydrogels constructed by a hybrid crosslinking strategy for pacemaker pocket infection prevention. (1st October 2020) - Dong, Quanbin; Zhong, Xuepeng; Zhang, Yiqing; Bao, Bingkun; Liu, Liang; Bao, Huihui; Bao, Chunyan; Cheng, Xiaoshu; Zhu, Linyong; Lin, Qiuning
Highlights: A modification strategy of hyaluronic acid (HA) by bisepoxy compound is reported. The modified HA micro-gel shows stable structure and injectable property. Chlorhexidine further crosslinks the micro-gel by electrostatic interaction with HA. The CHA/CHX gel shows good moldable property to reduce the extra CIED pocket space. The CHA/CHX gel can kill bacterias in vitro and in vivo to prevent CIED infection. Abstract: In this study, we developed an injectable antibacterial hydrogel based on hyaluronic acid (HA) and chlorhexidine (CHX) for cardiovascular implantable electronic device (CIED) infection treatment. To balance stability and moldability, the HA scaffold was pre-crosslinked by 1, 4-butanediol diglycidyl ether (BDDE) and then ground to form an HA microgel (CHA). Then, the antibacterial agent CHX was further crosslinked in the CHA microgel through electrostatic interactions between CHA and CHX to obtain hybrid crosslinked hydrogels (CHA/CHX). These hydrogels exhibited shear-thinning/self-recovery behavior, allowing easy injection into the CIED pocket and good matching with the pocket shape without extra space requirements, which represents an improvement on previously reported methods. In vitro and in vivo antibacterial tests showed that the CHA/CHX hydrogels had both good biocompatibility and very effective antibacterial action. The above results indicated that the CHA/CHX hydrogels would be an excellent candidate for CIED pocket infection treatment.